A broadly cross-reactive monoclonal antibody against hepatitis E virus capsid antigen - Kubickova, Barbara; Schenk, Jörg A.; Ramm, Franziska; Markuškienė, Kornelija; Reetz, Jochen; Dremsek, Paul; Tamosiunas, Paulius Lukas; Cepulyte, Laima; Trinh, Hoai Anh; Scholz, Johannes; Memczak, Henry; Hovestädt, Marc; et al. (Applied Microbiology and Biotechnology, 2021)
To generate a hepatitis E virus (HEV) genotype 3 (HEV-3)-specific monoclonal antibody (mAb), the Escherichia coli-expressed carboxy-terminal part of its capsid protein was used to immunise BALB/c mice. The immunisation resulted in the induction of HEV-specific antibodies of high titre. The mAb G117-AA4 of IgG1 isotype was obtained showing a strong reactivity with the homologous E. coli, but also yeast-expressed capsid protein of HEV-3. The mAb strongly cross-reacted with ratHEV capsid protein derivatives produced in both expression systems and weaker with an E. coli-expressed batHEV capsid protein fragment. In addition, the mAb reacted with capsid protein derivatives of genotypes HEV-2 and HEV-4 and common vole hepatitis E virus (cvHEV), produced by the cell-free synthesis in Chinese hamster ovary (CHO) and Spodoptera frugiperda (Sf21) cell lysates. Western blot and line blot reactivity of the mAb with capsid protein derivatives of HEV-1 to HEV-4, cvHEV, ratHEV and batHEV suggested a linear epitope. Use of truncated derivatives of ratHEV capsid protein in ELISA, Western blot, and a Pepscan analysis allowed to map the epitope within a partially surface-exposed region with the amino acid sequence LYTSV. The mAb was also shown to bind to human patient-derived HEV-3 from infected cell culture and to hare HEV-3 and camel HEV-7 capsid proteins from transfected cells by immunofluorescence assay. The novel mAb may serve as a useful tool for further investigations on the pathogenesis of HEV infections and might be used for diagnostic purposes. KEY POINTS: • The antibody showed cross-reactivity with capsid proteins of different hepeviruses. • The linear epitope of the antibody was mapped in a partially surface-exposed region. • The antibody detected native HEV-3 antigen in infected mammalian cells.